Workshop Pengolahan Sampah Rumah Tangga Organik menjadi Pupuk Organik Cair - Bagaskoro, Angga Dwi; Juliandara, Luthpiyah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Household waste is one of the biggest waste contributors to the environment. We can handle household waste by separating organic and inorganic waste. Kitchen waste is very useful and can be used like vegetable and fruit leftovers or rotting food. This waste will be processed into fertilizer. In addition to meeting the needs of nutrients in plants, by making organic fertilizer we will reduce too much waste. This activity is in collaboration with the surrounding community in Sumbersari Village. The purpose of this community service is to be able to provide information regarding household waste and the processing of organic waste into post fertilizer. This community service was carried out with a workshop on processing organic waste into compost which was attended by 15 participants. This activity begins with the delivery of material, discussion, demonstration of organic waste processing and ends with questions and answers to the workshop participants. Therefore, the community must increase awareness of the importance of carrying out 3R efforts, namely Reuse; Reduce; and Recycling.